INVASIVE PLANTS IN MOUNTAINOUS REMNANT FOREST: RECOMMENDATION FOR CHOOSING BEST DECISION FOR INVASIVE SPECIES MANAGEMENT OF Cestrum aurantiacum Lindl. - Junaedi, Decky Indrawan (Buletin Kebun Raya, 2012)
Cestrum aurantiacum Lindl. is an exotic species found in native remnant forest of GPNP which is located inside the Cibodas Botanic Garden (CBG). Risk assessment is an important tool to choose best decision for invasive plant management.Â  Risk assessment analysis on C. aurantiacum in Cibodas Botanic Garden was conducted using Multi Criteria Decision Analysis (MCDA) method.Â  Analytical Hierarchy Process (AHP) used in the valuation process. Three sub-criteria used: minimizing the ecological impact, minimizing the management cost, and maximizing the public acceptance. Five management alternatives were used: do nothing (DN), eradication (E), containment (C), bio-control (BC) and harvesting (H). Harvesting (H) recommended as the best management decision for C. aurantiacumin at CBG remnant forest. This harvesting decision is not only creating environment/ ecosystem remediation but also as sources of fund in the management activity of the area.